Deep Ecosemiotics: Forest as a Semiotic Model - Maran, Timo (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2019)
Many concepts used in semiotics today are derived from linguistics, philosophy, literature studies and other fields. Yet a genuinely ecosemiotic approach, requires modelling tools that go beyond imagery based on human culture and communication. In this paper, I develop an ecosemiotic research model that uses “forest” as its primary ground. Basing myself on the Tartu-Moscow school of cultural semiotics, I introduce modelling as an analytic method. Then I describe properties of the forest as an ecosystem as well as its experiential meaning for humans. The forest model can be applied in studying common objects of ecosemiotics, but it can also be mirrored back to the objects of general, cultural or social semiotics. The paper concludes with suggestions on developing the forest model in practical research.